Design and Production of an Instant Coffee Product Based on Greek Coffee Oil: Study of the Effect of Storage Conditions on Product Aroma and Quality - Efimia Dermesonlouoglou; Vassiliki Palaioxari-Kampisiouli; Dimitrios Tsimogiannis; Petros Taoukis (Beverages)
The objective of this study was to obtain and evaluate a coffee aroma extract/oil with sensorial attributes close to the original brew of Greek coffee for use in an instant Greek coffee powder. The oil was obtained directly from commercial Greek coffee by solid-liquid extraction using hexane as a solvent and treated with a series of hexane-ethanol mixtures (0:10, 1:4, 1:9) to remove the intense roasted flavor of the crude coffee oil obtained by hexane; the de-oiled coffee was used for the recovery of water-soluble compounds, and the produced water extract was freeze-dried. The aromatic volatiles of the coffee oil samples were analyzed by using a purge-and-trap device coupled to GC-MS, as well as sensory analysis. The instant Greek coffee powder was produced by mixing the freeze-dried base (74.4%) with the extract derived after treatment of the crude oil with hexane-ethanol mixture 1:4 (18.2%) and foaming agent (7.4%). Two different materials were studied as bases: instant coffee (F3Gr-D) and ground Greek coffee (reference sample, CGr). The shelf-life stability of the produced powders was examined at three storage temperatures (25, 45, 60 °C). Instrumental analysis (purge-and-trap GC-MS) of aroma and sensory analysis (aroma, taste, staling, total sensory quality on a 1–9 hedonic scale) was conducted. Aroma loss (furfuryl alcohol, furfural, dimethyl pyrazines, ethyl methyl pyrazines) and scores for sensory attributes during storage were modeled using 1st and 0-order reaction kinetics, respectively. The storage temperature effect was expressed by the Arrhenius model (activation energy Ea). According to the results, the developed instant coffee powder presented satisfactorily the aroma characteristics of regular Greek coffee. The shelf life for the instant Greek coffee powder was estimated as 80 days (air packed) (based on 20% retention of furfuryl alcohol that was the most abundant aromatic volatile of Greek coffee aroma, ground as well as extract oil).